Phenomenological Study of Compliance with Paying Dues by Independent Participants in the National Health Insurance Program in Medan City in 2023 - Liory Olganita Banjarnahor; R Kintoko Rochadi; Jasmen Manurung (Jurnal Info Sains : Informatika dan Sains, 2023)
The objective of this study is to determine and analyze the causing factors of non-compliance in paying National Health Insurance contributions (JKN) by independent participants and to find out the efforts made by the Social Security Agency on Health (BPJS) to increase compliance in paying JKN contributions and the efforts made by the Medan Government through Health Department to taking care the independent participants in arrears. This is a qualitative study with a phenomenological approach. Data collection is carried out by in-depth interviews and documentation. The informants in this research are Independent JKN Participants, BPJS Stakeholders and Health Department Stakeholders. The data processing uses the Miles Hubberman method. The results of the study show that the causing factors of non-compliance with paying JKN contributions are due to large amount of arrears, They are still able to seek health treatment using their ID card at the Puskesmas (Community Health Center), Economic Factors, Number of dependents (family members) and an Increasing in dues. Efforts that have been made by Health BPJS to increase compliance in paying JKN contributions are by providing convenience in payment methods, there are efforts to establish communication with independent JKN participants (through tele-collecting efforts, conduct WhatsApp blasts for delinquent participants, visit delinquent participants through JKN cadres, and conduct outreach in sub-districts and crowded places), as well as the existence of a Phased Payment Plan (REHAB) program where the arrears can be paid in installments. Efforts made by the Health Department and the Medan City Government include switching independent participants to JKN Contribution Assistance Recipient (PBI) participants and the Universal Health Coverage (UHC) Program through the Medan Berkah Health Insurance (JKMB) of Medan City.